The Nature Of Teacher In Islamic Education - Sarah Rhausan Nisa; Rika Afrillia (Proceeding International Seminar of Islamic Studies, 2019)
This study is entitled The Nature of Teachers in Islamic Education as an object in the perspective of Islamic Education Philosophy The problem that arises is that many teachers still do not know the nature of being a teacher and there are still teachers who do not fully know what their duties as a teacher are. Is the teacher's job only as an educator in Islamic education. The purpose of the research is to find out the true nature of a teacher and to know the task of a teacher. The method used is library research, qualitative. It was found that the true nature of the teacher and the task as a teacher there are several points in Islamic education and therefore the teacher will know what the true nature is and know what the tasks are as teachers in Islamic education.